Cabrogal to Fairfield City : a history of a multicultural community - Gapps, Stephen; Fairfield (N.S.W.). Council (Wakeley, N.S.W. : Fairfield City Council, 2010)
This book allows us to dig deeply into the rich details of everyday life in the past and in the present. This meticulous look at the Fairfield area gives us the satisfying experience of recognising our everyday surroundings and hearing the pepople we know speak to us from the book's pages.
Includes index.
Ill. on end papers.
Bibliography: p. 465-480.
Keywords: Cities and towns -- New South Wales -- Fairfield -- History; Immigrants -- New South Wales -- Fairfield -- History; Aboriginal Australians -- New South Wales -- Fairfield -- History; Local history; Dharug / Daruk / Darug people (S64) (NSW SI56-05); Colonisation; Material culture; Hunting, gathering and fishing; Social organisation - Clans; Subsistence and economy; Race relations - Violent; Settlement and contacts - Ethnic groups, immigration and multiculturalism; Fairfield (N.S.W.) -- History; Fairfield (N.S.W.) -- Social conditions; Fairfield (Sydney NSW SI56-05); Smithfield (Sydney NSW SI56-05); Cabramatta (Sydney NSW SI56-05); Georges River (S Sydney NSW SI56-05)